Web Service Composition via Supervisory Control Theory - Hikmat Farhat (IEEE Access, 2018)
We present a model for the service composition problem and relate it to the classical problem of supervisory control in discrete event systems. In particular, we show how the orchestrator in the first problem transparently maps to the controller in the second problem. Moreover, the community of web services plays the role of the plant in supervisory control and both formalisms are related using the notion of bisimulation. We also show how modal specifications can be used in both settings.